EfICACIA DE LAS ASOCIACIONES EMPRESARIALES PARA LA PARTICIPACIÓN DE LAS PYME EN EL NEGOCIO DE LA EXPORTACIÓN - Ramírez Huerta, Valiente Pantaleón (2013)
This study set out to answer the question what forms of business associations are effective participation of SMEs in the export business?. The results show that in Punjab between 2007 and 2011, 24 associations were formed for export of which 11 are consortia, 13 franchises, and none in sub contracting, licensing or joint venture brand. Therefore our hypothesis “business associations are effective participation of SMEs in the export business” is accepted. It has been determined that the most effective are franchises and consortia and others are unusual. Require business consortia agreements by consensus, while franchises are more effective because the direct relationship between the franchisor and franchisee is independent in each case. The results will benefit SMEs to make appropriate decisions to achieve their goals in terms of their participation in international trade through business associations, thereby contributing to economic growth and social welfare of the country.